Formation of Information and Communication Culture in the Modern Digital Environment - Yorievich, Tairov (Indonesian Journal Publisher, 2024)
The purpose of the research is to study the problems of formation of information and communication culture in the modern digital environment. The process of creation, use and distribution of knowledge in modern post-industrial society has significantly accelerated due to the active development of new information technologies.